Tracing Technological Pedagogical Content Knowledge (TPACK) on Practical EFL Teachers in Writing Context - Siti Ayu Surayya; Maman Asrobi (Universitas Hamzanwadi, 2020)
With the world demand to provide digital school, this study examines how the integration between technology, pedagogy and content knowledge in writing context as the part of TPACK framework on the practical EFL teachers. The samples of this study are 27 of practical English teachers divided into three level of achiever (low, middle, and high. They were taking the Writing and Assessment courses as the part of their education to achieve the bachelor degree in Universitas Hamzanwadi, a private university in Lombok, Indonesia. This research took about six months of teaching and learning process. The observation and document results of the practical EFL teachers become the data primer of this study since the researchers act directly as the lecturer in the writing course. This study uses qualitative research as it investigates a process of teaching learning that lasted several months and happened in a particular setting. The result of study showed that the practical teachers’ writing content and pedagogy knowledge were better than their technological knowledge. Furthermore, the high achiever of practical EFL teachers perform a good TPK and TCK rather than they who come from middle and low achiever.